2011
DOI: 10.1177/0098628311411794
|View full text |Cite
|
Sign up to set email alerts
|

Student and Faculty Perceptions of E-Feedback

Abstract: This article presents student and faculty ratings of electronic editing (EE) functions (i.e., track changes, insert comments, highlighting) as used for e-feedback on written assignments. Students reported increased convenience, clarity of expectations, amount of feedback, and writing ability as well as substantial improvement in EE skills compared to paper-based methods. Also, ratings and use of e-feedback were positively correlated with final report grades. To further explore the role of e-feedback in psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…Reduced travel time in particular also affects students" perception of the quality of their work to be submitted because the saved time can be used towards the assignment, particularly with regards to proofreading (Hast & Healy, 2018). Time also means that accessing feedback online makes the process more convenient and immediate for students (Grieve et al, 2016;Hast & Healy, 2018;McCabe, Doerflinger, & Fox, 2011;McGrath & Atkinson-Leadbeater, 2016). They are able to access their feedback no matter where they are in space or time (Hast & Healy, 2018;Palmer, 2005;Timmis et al;Turney et al, 2009), which is entirely in line with the net generation who seeks to engage with their educational experience whenever and wherever they want to (Gosper et al, 2013).…”
Section: Key Advantages Of Online Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced travel time in particular also affects students" perception of the quality of their work to be submitted because the saved time can be used towards the assignment, particularly with regards to proofreading (Hast & Healy, 2018). Time also means that accessing feedback online makes the process more convenient and immediate for students (Grieve et al, 2016;Hast & Healy, 2018;McCabe, Doerflinger, & Fox, 2011;McGrath & Atkinson-Leadbeater, 2016). They are able to access their feedback no matter where they are in space or time (Hast & Healy, 2018;Palmer, 2005;Timmis et al;Turney et al, 2009), which is entirely in line with the net generation who seeks to engage with their educational experience whenever and wherever they want to (Gosper et al, 2013).…”
Section: Key Advantages Of Online Feedbackmentioning
confidence: 99%
“…Particularly in light of the benefits afforded by remote access to feedback, there may be delays in the clarification process because students may be accessing their feedback at times where staff are not immediately reachable. This lack of a relationship with the online marker can have knock-on effects, leading towards depersonalisation and reduced self-regulated learning (McCabe et al, 2011;Parkin et al, 2012) and can, in turn, impede the issue of interpretation. In not being able to clarify feedback or having concerns with potential misinterpretation, there is a reduced perceived efficacy to engage (Hast, 2017).…”
Section: Areas Of Continued Concernmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, interpretation and use of feedback may differ between students, suggesting that an approach that reduces discussion opportunities may not necessarily be most suitable (Hattie & Timperley, 2007;McLoughlin & Luca, 2006). Finally, an online approach may in fact contribute towards higher levels of depersonalization, which may achieve the very opposite of self-regulated learning (McCabe, Doerflinger, & Fox, 2011;Parkin, Hepplestone, Holden, Irwin, & Thorpe, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, empirical and qualitative evidence suggests that students prefer to have writing feedback delivered electronically. McCabe, Doerflinger, and Fox (2011) concluded that students found electronic feedback to be more convenient than handwritten feedback. Students also reported that electronic feedback included more substantive comments from instructors, which improved their writing to a greater degree than handwritten feedback.…”
mentioning
confidence: 99%